2020
DOI: 10.3390/app10249130
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Temperature and Time in Centrifugation-Assisted Freeze Concentration

Abstract: Centrifugation is a technique applied to assist in the freeze concentration of fruit juices and solutions. The aim of this work was to study the influence of the time–temperature parameters on the centrifugation process as a technique applied to assist in the first cycle of the freeze concentration of blueberry juice. A completely randomized 4 × 3 factorial design was performed using temperature and time as the factors, and the response variables included the percentage of concentrate, efficiency and solutes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Santana et al. (2020) also calculated the concentration efficiency for blueberry juice when subjected to the centrifugation‐assisted freeze concentration, and likewise, individual factors did not affect this response. A different result was noted for Y (Figure 2c), where it was observed that all individual factors and two interactions had a significant effect on the response.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Santana et al. (2020) also calculated the concentration efficiency for blueberry juice when subjected to the centrifugation‐assisted freeze concentration, and likewise, individual factors did not affect this response. A different result was noted for Y (Figure 2c), where it was observed that all individual factors and two interactions had a significant effect on the response.…”
Section: Resultsmentioning
confidence: 99%
“…This situation is correlated with the final temperature of the process, since longer rotation times of the centrifuge generate an increase in the rotor temperature, causing that part of the ice to transform into water and be expelled to the outside together with the concentrate, harming the phase separation of the system. Conversely, an insufficient centrifugation time would not achieve an efficient separation, and thus, the process parameters would indicate low concentrate recovery percentages (Santana et al., 2020). Therefore, these results (higher CI values when time is shorter) could be justified due to the ice fraction staying relatively intact (without breaking and/or thawing) employing 45 min as centrifugation time, and thus, only freeze concentrate was extracted from the ice fraction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, other techniques with fewer costs and better yields are being studied at laboratory and pilot scale, including centrifugation‐assisted block cryoconcentration (CABC) and vacuum‐assisted block cryoconcentration (VABC). Some research groups have worked with both techniques independently for several food products, with promising results, such as sucrose solutions both by VABC (Petzold et al, 2013) and CABC (Petzold & Aguilera, 2013), blueberry juice by VABC (Orellana‐Palma, Petzold, Andana, et al, 2017) and by CABC (Casas‐Forero et al, 2021; Orellana‐Palma, Petzold, Guerra‐Valle, & Astudillo‐Lagos, 2017; Petzold et al, 2015; Santana et al, 2020), and orange juice by VABC (Petzold et al, 2017, 2019) and by CABC (Orellana‐Palma, González, & Petzold, 2019; Orellana‐Palma, Petzold, Andana, et al, 2017). However, to the authors’ knowledge, the two methods have not been compared to evaluate which of them gives better results.…”
Section: Introductionmentioning
confidence: 99%